2020
DOI: 10.1186/s12864-020-6767-x
|View full text |Cite
|
Sign up to set email alerts
|

Multipathway synergy promotes testicular transition from growth to spermatogenesis in early-puberty goats

Abstract: Background The microscopic process of postnatal testicular development in early-puberty animals is poorly understood. Therefore, in this study, 21 male Yiling goats with average ages of 0, 30, 60, 90, 120, 150 and 180 days old (each age group comprised three goats) were used to study the changes in organs, tissues and transcriptomes during postnatal testicle development to obtain a broad and deep insight into the dynamic process of testicular transition from growth to spermatogenesis in early-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 65 publications
3
15
0
Order By: Relevance
“…The rapid development of spermatogenic cells in testis during the first estrus has also been observed in other animals. At the onset of puberty (90 days old), large cross-sectional seminiferous tubules, thick spermatogenic epithe lial cells and obvious sperm were observed [19], which was consistent with our observation in Hu sheep. The results showed that there were differences in the estrus stage among different breeds.…”
Section: Classification Of Transcription Factors Of the 5' Upstream Region Expressed In Testissupporting
confidence: 92%
See 1 more Smart Citation
“…The rapid development of spermatogenic cells in testis during the first estrus has also been observed in other animals. At the onset of puberty (90 days old), large cross-sectional seminiferous tubules, thick spermatogenic epithe lial cells and obvious sperm were observed [19], which was consistent with our observation in Hu sheep. The results showed that there were differences in the estrus stage among different breeds.…”
Section: Classification Of Transcription Factors Of the 5' Upstream Region Expressed In Testissupporting
confidence: 92%
“…Go enrichment analysis by Panther website(http://geneontology.org/). Cattle (Bos taurus) gene bank with high homology with sheep was selected as the template, and the results of enrichment retained the genes with FDR value less than 0.05 significant enrichment [19]. Ggplot2 package of R language is used to draw go enrichment analysis results for visualization.…”
Section: Sequence Characterization Of Tf Binding Sites Of Cry1 In Sheepmentioning
confidence: 99%
“…Together with our results, these reports indicate that ATP10A and SRGAP3, as putative candidate genes for sexual precocity, are regulated not only by genetic factors but also by environmental and epigenetic factors. The second compelling piece of evidence for the involvement of the differentially methylated genes in sexual maturity of HM bulls is provided by a study using Yiling goats, a native Chinese breed exhibiting precocious puberty, as a model to investigate the changes in the testis transcriptome that parallel the post-natal development of testis (Bo et al, 2020). In that study, 120 days of age was identified as the transition point at which testis weight dramatically increases and spermatogenesis becomes functional in Yiling goats; two genes targeted by differential methylation in our study, ALDOB and PIGR, are listed as "hub genes" whose expression is modified during this transition.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, 120 days of age was identified as the transition point at which testis weight dramatically increases and spermatogenesis becomes functional in Yiling goats; two genes targeted by differential methylation in our study, ALDOB and PIGR , are listed as “hub genes” whose expression is modified during this transition. Although not listed as “hub genes” by Bo et al (2020) , we identified several genes involved in spermatid differentiation or highly expressed post-meiotically, such as RARB , ADCY8 , and OSBP2 (relevant references are provided in Supplementary Table 9 ). We also identified many differentially methylated genes involved in cytoskeleton remodeling, cilium growth and cell junction, such as ACTN1 , GSN , MTMR7 , PACRG , TUBB2B , and ARC .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from being classi ed under the GO "Development processes" in the Afrino gene DAVID analysis, "Sperm capacitation" is another GO biological process of the BSPH1 gene [25] (https://david.ncifcrf.gov/). The HDAC9 gene was downregulated in 90-day old male goat kids and this was conducive to the vigorous development of spermatogenesis in this period [55] (Bo et al, 2020). TRPM8 is a testosterone receptor [56,57] (Asuthkar et al, 2015a; Asuthkar et al, 2015b) and TRPM8 channels may be implicated in various physiological processes regulated by androgens [58] (Sutton et al, 2018).…”
Section: Genome-wide Association Studymentioning
confidence: 99%